Bahasa Inggris - Gina Mufidah; Karuniana Dianta A.S; Siti Fatimah Zahra (Yayasan Education and Social Center, 2022)
Food purchase through the GrabFood delivery feature for people in DKI Jakarta, which is proven to help humans in their daily lives, is determined and influenced by many factors. In this study, the factors studied were consumer trust and the use of online motorcycle taxi services. This study aims to determine the effect of consumer trust and the use of online motorcycle taxi services on food purchases through the GrabFood Delivery feature for people in DKI Jakarta (Non-Thousand Islands). This research is quantitative. The object of this study is the people of DKI Jakarta aged eighteen years and over who use the GrabFood delivery feature, with an unknown population. The sample in this study amounted to 115 respondents, determined using the Malhotra formula by multiplying the number of sub-indicators by five. The analytical method used in this research is multiple regression analysis which includes several tests, namely reliability validity test, descriptive analysis, classical assumption test and statistical test. There are several indicators of each variable that state the least results. Namely, there is an indicator of company image on the consumer trust variable, an indicator of the ease of using online motorcycle taxi services and the last indicator of the number of purchases on the food purchase variable. The results of this study indicate that consumer trust and the use of online motorcycle taxi services partially affect food purchases. The variables of consumer confidence and the use of online motorcycle taxi services simultaneously have a positive and significant effect on food purchases which can be proven by the results of several tests that have been carried out using the SPSS 25 application